(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
In aesthetic surgery, shape-altering procedures are increasingly being performed on the human body at the request of patients or out of medical necessity to improve their well-being. Liposuction is the most frequently performed aesthetic procedure. Additive manufacturing, sensors and data are used to optimise the procedure and the medical devices required for it. 3D-printed adapters for liposuction cannulas enable effective sensor integration and rapid prototyping of corresponding medical components. This shortens development times and costs and enables customisation to the user’s needs.